The current status of kidney transplantation in Nigerian children: still awaiting light at the end of the tunnel (2020)
Background Kidney transplantation (KT) is the gold standard treatment for childrenwith chronic kidney disease stage 5 (CKD5). It is easily accessible in well-resourced countries, but not in low/middle-income countries (LMICs). We present, a multicenter experience of paediatric KT of children domiciled in Nigeria. We aim to highlight the challenges and ethical dilemmas that children, their parents or guardians and health care staff face on a daily basis. Methods A multicentre survey of Nigerian children who received KTs within or outside Nigeria from 1986 to 2019 was undertaken using a questionnaire emailed to all paediatric and adult consultants who are responsible for the care of children with kidney diseases in Nigeria. Demographic data, causes of CKD5, sources of funding, donor organs and graft and patient outcome were analysed. Using Kaplan-Meier survival analysis, we compared graft and patient survival. Results Twenty-two children, aged 4–18 years, received 23 KTs, of which 12 were performed in Nigeria. The male-to-female ratio was 3.4:1. Duration of pre-transplant haemodialysis was 4–48 months (median 7 months). Sixteen KTs were self-funded. State governments funded 3 philanthropists 4 KTs. Overall differences in graft and patient survival between the two groups, log rank test P = 0.68 and 0.40, respectively were not statistically significant. Conclusions The transplant access rate for Nigerian children is dismal at < 0.2%. Poor funding is a major challenge. There is an urgent need for the federal government to fund health care and particularly KTs